Knowledge and Attitude of Farmers towards Soil Testing - Solanki, Ratan Lal; Dhaker, Sanjay Kumar; Nagar, Gajendra (Current Research Progress in Agricultural Sciences Vol. 9, 2025)
Soil testing is a scientific technique used for assessing the external nutrient needs of crops to achieve a profitable response. It provides current qualitative information on the nutrient and the nutrient-supplying capacity of the soil. It is the basis for making scientifically sound and management decisions about the requirement of specific kinds of fertilizers and soil amendments. In general, a simple soil test determines the EC, pH, organic carbon, phosphorus, and potassium status of soil. Based on the estimated value, soils are categorized into two classes, viz., low and medium with respect to a particular nutrient. The study was conducted in Chittorgarh district in ten adopted villages of KVK, Chittorgarh, Rajasthan and 10 farmers randomly selected from each village that have availed soil-testing technique. The study reveals that the majority of respondents had poor knowledge and a maximum knowledge gap was observed in proper technique of sampling for fruit plants and normal crops. The study also shows a positive attitude, as most adopters (76 %) did not agree with the statement that "soil testing is wastage" of time and money and It was also observed that the majority of farmers agreed (72 %) with the statement "soil testing is necessary for better crop production". The efforts should be made by KVK and the Department of Agriculture to encourage the farmers to adopt soil testing practices by organizing soil testing training programmes and campaigns, especially on the soil testing process. By adopting the soil testing practices, the farmers also reduced the large unnecessary chemical fertilizer consumption and the judicious use of chemical fertilizers could be popularized. Therefore, as per the problem faced and suggested by the farmers, more scientific and educational training and facilities are required to disseminate the technology at large.